2017
DOI: 10.1038/onc.2017.70
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase processing of PTHrP yields a selective regulator of osteogenesis, PTHrP1–17

Abstract: Parathyroid hormone-related protein (PTHrP) is a critical regulator of bone resorption and augments osteolysis in skeletal malignancies. Here we report that the mature PTHrP hormone is processed by matrix metalloproteinases to yield a stable product, PTHrP. PTHrP retains the ability to signal through PTH1R to induce calcium flux and ERK phosphorylation but not cyclic AMP production or CREB phosphorylation. Notably, PTHrP promotes osteoblast migration and mineralization in vitro, and systemic administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Thus, Notch3 is likely operating on the bone tumor microenvironment through at least one other mechanism. MMP-3 is known to promote the cleavage of PTHrP produced by cancer cells, which stimulates osteoblast migration and mineralization in vitro but lacks the osteolytic function associated with full length PTHrP (32). PTHrP also promotes osteoblast proliferation (33).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Notch3 is likely operating on the bone tumor microenvironment through at least one other mechanism. MMP-3 is known to promote the cleavage of PTHrP produced by cancer cells, which stimulates osteoblast migration and mineralization in vitro but lacks the osteolytic function associated with full length PTHrP (32). PTHrP also promotes osteoblast proliferation (33).…”
Section: Discussionmentioning
confidence: 99%
“…We further found that this osteolytic suppression is MMP3-dependent. MMP-3 is known to promote the cleavage of PTHrP produced by cancer cells, which stimulates osteoblast migration and mineralization in vitro but lacks the osteolytic function associated with full length PTHrP (39). PTHrP also promotes osteoblast proliferation (40).…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal malignancies, for example, MMPs have been shown to process many of the factors that drive cancer-bone interactions, including TGF-β, RANKL, and insulin growth factor (IGF) [135,136,137]. PTHrP has also been identified as a novel substrate of MMP-2, -3, -7, -9, and -13, which predominantly generate PTHrP1–17, 18–26, and 27–36 amino acid products [62]. Notably, the novel PTHrP1–17 product retains the ability to signal through PTH1R whereby it induces the osteogenic activities of full length PTHrP1–36, but it does not impact RANKL and osteoclast formation in vivo, even when dosed continuously.…”
Section: Proteolytic Control Of Pthrp Functionmentioning
confidence: 99%